Mengenal Karakteristik Mad’u Masyarakat Muslim - Nabila, Farah Nurul (Mekomda: Media Komunikasi Dakwah, 2023)
Research on the characteristics of mad'u must indeed be done by a da'i to be able to maximize his da'wah message. Because then da'i will be easier to influence the object of da'wah for the better. In this case, one example of a da'I must know the character of the Muslim community that will be the target of his da'wah. Starting from his educational background, environment and things that can be understood by his mad'u. The characteristics of Mad'u in Muslim society are very important in da'wah and the strategy of introducing Islamic values. Mad'u is a person who accepts invitations and calls to Islam. In Muslim society, Mad'u can be classified based on various aspects such as gender, age, educational background, cultural background, economic background, social status, profession, and so on. Knowing the characteristics of Mad'u in Muslim society is very important to understand how they receive and respond to da'wah. An effective da'wah strategy must consider various aspects of Mad'u characteristics, including intellectual, psychological, and theological capacities, as well as the various categories of Mad'u found in society.